Food peptides: purification, identification and role in the metabolism. (February 2016) - Arroume, Naima; Froidevaux, Rénato; Kapel, Romain; Cudennec, Benoit; Ravallec, Rozenn; Flahaut, Christophe; Bazinet, Laurent; Jacques, Philippe; Dhulster, Pascal
Highlights: Food and marine proteins as source to produce bioactive peptides. There is a high biodiversity of bioactive peptides from animal or plant sources. Bioactive peptides play an important role in energy homeostasis. Peptidome identification is needed to understand the bioactivity. Controlled bioprocesses are needed for the separation of bioactive peptides. Abstract : The search for new active molecules from food protein hydrolysates represents a real challenge for animal feed, aquaculture, as fertilizer, but also in cosmetics and pharmacological fields. The constant discovery of molecules with biological activities continually brings new insights into the complex mechanisms involved in vivo . However, it remains difficult to conclude about the structure, amino acid composition, size or the physicochemical properties necessary for the activity. This review will highlight the research carried out to determine the physiological role of these peptides and the development of new tools for their production and study.